PENERAPAN PERMAINAN SIMULASI SEBAGAI TEKNIK BIMBINGAN KELOMPOK UNTUK MENYELESAIKAN KONFLIK - Salmiati, Salmiati; Amiruddin, Amiruddin (JURKAM: Jurnal Konseling Andi Matappa, 2017)
The aim of this study were (1) To determine the ability to resolve conflicts before the picture was given a simulation exercise in SMP Negeri 3 Bungoro. (2) To determine the ability to resolve conflicts following description given simulation exercise in SMP Negeri 3 Bungoro. (3) To determine the effect of the application of simulation games as group counseling techniques for improving the ability of resolving the conflict in SMP Negeri 3 Bungoro. This research is an experimental research using a quantitative approach. The population is all students of SMPN 3 Bungoro with a sample of 30 students. The technique of collecting data using questionnaires, observation and documentation. The results of the research are (1) picture capability resolve conflicts student SMP Negeri 3 Bungoro village Bori Appaka District of Bungoro before given training before being given the application of simulation / training application simulation games usually are in the unfavorable category for the highest value of 50%. (2) The description of the ability of resolving conflicts student SMP Negeri 3 Bungoro village Bori Appaka District of Bungoro after given training simulation application. generally in good category with the highest frequency of 80%. (3) The results of the t-test data analysis with the comparison of the t (2.502)> t table (2.045) so it can be interpreted that there has been a positive and significant changes in the ability to improve students resolve conflicts through simulated game activity as group counseling techniques.